2006
DOI: 10.1017/s0025315406013178
|View full text |Cite
|
Sign up to set email alerts
|

Early development of the red king crab Paralithodes camtschaticus from the Barents Sea reared under laboratory conditions: morphology and behaviour

Abstract: Morphology of larval, postlarval, and early juvenile stages of the red king crab is described and illustrated from laboratory reared material; attention is directed to certain aspects of morphology not previously considered. Some behavioural patterns are clarified, with special emphasis on locomotion and feeding. Morphological criteria for distinguishing the first two juvenile stages are proposed; additional morphological criteria for distinguishing zoeal stages are reported. Data on development and growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
1
24
1
Order By: Relevance
“…After the eggs have hatched, the female crabs moult and produce another clutch of eggs which become fertilized by males; they then extrude the fertilized eggs, which are carried beneath the abdomen until the next spring. The pelagic larval period lasts for about two to three months before they settle in shallow water in early summer (Epelbaum et al 2006).…”
Section: Benthic Invertebratesmentioning
confidence: 99%
“…After the eggs have hatched, the female crabs moult and produce another clutch of eggs which become fertilized by males; they then extrude the fertilized eggs, which are carried beneath the abdomen until the next spring. The pelagic larval period lasts for about two to three months before they settle in shallow water in early summer (Epelbaum et al 2006).…”
Section: Benthic Invertebratesmentioning
confidence: 99%
“…The Alaska King Crab Research Rehabilitation and Biology (AKCRRAB) programme was created in 2006 to assess the feasibility of stock enhancement for king crabs in Alaska and expanded on previous rearing technologies (Nakanishi & Naryu ; Nakanishi , ; Epelbaum et al . ; Kovatcheva et al . ; Stevens ,b).…”
Section: Introductionmentioning
confidence: 99%
“…There are two main factors that could explain that L. santolla larvae are more resistant to ammonia exposure: one factor is associated with its significant size compared with other decapods' larvae, and the other factor is that they do not depend on exogenous food sources (Amin et al 2003). Concerning the first factor, Campodónico (1971) reported that zoeae I of L. santolla have a carapace length of 3.75 ± 0.14 mm (total length of 6 mm; Boschi et al 1984), while this parameter in the same stage of related commercial species like Paralomis granulosa and Paralithodes camtschaticus is between 2.75 and 3.25 mm for the former, and 1.39 ± 0.03 mm for the latter (Epelbaum et al 2006;McLaughlin et al 2003). Furthermore, zoeae I of P. pelagicus, a more sensitive species to ammonia, presented values between 0.44 and 0.54 mm in carapace length (Josileen and Menon 2004).…”
Section: Discussionmentioning
confidence: 99%